Proliferating Trichilemmal Tumor: A Case on the Nose of a 70-Year-Old Man - Marcia Ramos-; Marcius A. Peryassu; Bernardo C. Peryassu; Raphael C. Peryassu; Juan Piñeiro-Maceira; Marcia Ramos- (Karger Publishers, 2013)
The authors report a case of proliferating trichilemmal tumor on the tip of the nose of a man. This tumor is usually seen in women and on the scalp, and it shows trichilemmal keratinization on histopathology.